Gambaran Burnout pada Perawat di Instalasi Gawat Darurat (IGD) RSUD Al-Ihsan Provinsi Jawa Barat - Oktaviana, Mariska; Fitria, Nita; Mirwanti, Ristina (Universitas Malahayati, 2026)
ABSTRACT Burnout is a psychological problem resulting from emotional and interpersonal stress that occurs continuously in the workplace. The high workload of nurses can physical and psychological problems that can lead to burnout. This study amins to describe the incidence of burnout in emergency nurses at Al-Ihsan Hospital, West Java Province. The quantitative descriptive study design with total sampling of emergency nurses at Al-Ihsan Hospital, West Java Province (N=62). The instrument used was the Copenhagen Burnout Inventory (CBI), analyzed using univariate analysis. Data collection was carried out from 4-7 January 2025. The results of this study indicate that most respondents (83.9%) experienced low personal burnout, most respondents (79%) experienced low work-related burnout, and most respondents (83.9%) experienced low client-related burnout. The conclusion of this study is that there are emergency nurses who experience low personal burnout, work-related burnout, and client-related burnout. Based on the results of the study, it is suggested for institution to conduct stress management training programs and conduct training related to communication skills and training to improve the ability to adjust to carrying out multiple roles. It is also recommended for nurses to improve the quality of social support from both fellow nurses and nurse managers and implement workplace stretching exercise interventions to increase muscle flexibility and improve physical fitness. Keywords: Client-Related Burnout, Emergency Department, Nurses, Personal Burnout, Work-Related Burnout. ABSTRAK Burnout merupakan masalah psikologis akibat dari stres emosional dan interpersonal yang terjadi secara terus-menerus di tempat kerja. Tingginya beban kerja perawat dapat menimbulkan masalah fisik dan psikologis yang dapat berujung pada burnout. Penelitian ini bertujuan untuk mengetahui gambaran burnout pada perawat IGD RSUD Al-Ihsan Provinsi Jawa Barat. Rancangan penelitian deskriptif kuantitatif dengan total sampling perawat IGD RSUD Al-Ihsan Provinsi Jawa Barat (N=62). Instrumen yang digunakan adalah Copenhagen Burnout Inventory (CBI), dianalisis menggunakan analisis univariat. Pengambilan data dilakukan pada tanggal 4-7 Januari 2025. Hasil penelitian ini menunjukkan bahwa sebagian besar responden (83,9%) mengalami personal burnout yang rendah, sebagian besar responden (79%) mengalami work-related burnout yang rendah, dan sebagian besar responden (83,9%) mengalami client-related burnout yang rendah. Simpulan dari penelitian ini adalah personal burnout, work-related burnout, dan client-related burnout pada perawat IGD berada dalam kategori rendah. Berdasarkan hasil penelitian tersebut, disarankan bagi institusi untuk mengadakan program pelatihan manajemen stres dan melakukan pelatihan terkait keterampilan berkomunikasi dan pelatihan untuk meningkatkan kemampuan menyesuaikan diri untuk menjalankan peran ganda. Disarankan juga bagi perawat untuk meningkatkan kualitas dukungan sosial baik dari sesama perawat maupun manajer perawat dan menerapkan intervensi workplace stretching exercise guna meningkatkan fleksibilitas otot dan meningkatkan kebugaran fisik. Kata Kunci: Client-Related Burnout, Instalasi Gawat Darurat, Perawat, Personal Burnout, Work-Related Burnout.